The effect of hyperbranched poly(acrylic acid)s on the morphology and size of precipitated nanoscale (fluor)hydroxyapatite. Issue 30 (19th July 2017) - Shallcross, Laura; Roche, Kevin; Wilcock, Caroline J.; Stanton, Kenneth T.; Swift, Thomas; Rimmer, Stephen; Hatton, Paul V.; Spain, Sebastian G.
Abstract : Hydroxyapatite and fluorhydroxyapatite (F)HA nanoparticles were synthesised in the presence of branched poly(acrylic acid)s and compared to those synthesised in the presence of linear PAA. Abstract : Hydroxyapatite and fluorhydroxyapatite (F)HA nanoparticles were synthesised in the presence of branched poly(acrylic acid)s (PAA) synthesised via reversible addition–fragmentation chain transfer polymerisation and compared to those synthesised in the presence of linear PAA. Analysis of the resulting nanoparticles using Fourier transform infrared spectroscopy, powder X-ray diffraction and transition electron microscopy found that the polymer was included within the nanoparticle samples and affected their morphology with nanoparticles synthesised in the presence of branched PAA being more acicular and smaller overall.